Choice of the Parameters of the CUSUM Algorithms for Parameter Estimation in the Markov Modulated Poisson Process; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Burkatovskaya Yu. B. Yuliya Borisovna (2016, 2016)
Title screen